IGF1 and IGF2 specificities to the two insulin receptor isoforms are determined by insulin receptor amino acid 718 - Andersen, Mie (PLoS One, 2017)
METHODS: Alanine scan of insulin receptor (IR)-B exon 11 and site-directed mutagenesis of amino acid 718 in human IR-A and IR-B were performed. Ligand affinities to wild type and mutated receptors were studied by displacement of radioactive insulin in binding assay on secreted soluble midi receptors or solubilized semi-purified full length receptors stably expressed in Baby Hamster Kidney cells. Phosphorylation of IR in response to insulin, IGF1 and IGF2 was measured using ELISA. RESULTS: Insulin, insulin detemir and insulin glargine maximally showed two fold differences in affinity for human IR-A and IR-B, but IGF1 and IGF2 had up to 10 fold preference for IR-A. Alanine scan of exon 11 revealed that position 718 is important for low IGF1 affinity to IR-B. Mutational analysis of amino acid residue 718 in IR-A and IR-B demonstrated that charge is important for IGF1 and IGF2 affinity but not important for insulin affinity. The affinity of IGF1 and IGF2 for the mutant IR-A P718K was comparable to the wild type IR-B whereas the affinity of IGF1 and IGF2 for the mutant IR-B K718P was comparable to the wild type IR-A. Changes in affinity were also reflected in the IR activation pattern. CONCLUSION: Mutating position 718 in human IR-B to the proline found at position 718 in human IR-A increased IGF1 and IGF2 affinity to a level comparable to IR-A and mutating position 718 in IR-A to the lysine found at position 718 in IR-B decreased IGF1 and IGF2 affinity to a level comparable to IR-B, whereas a negatively charged glutamate did not. These changes in the affinities were also reflected in the IR phosphorylation pattern, meaning that position 718 is important for both affinity and activation of the receptor. It should be emphasized that none of the mutations affected insulin affinity, indicating that the mutations did not alter the overall receptor structure and that the effect is ligand specific.